The impact of the national security system on the prevention of security threats in the Republic of Serbia: attitudes of secondary school students - Kesić, Dušan B.; Radojević, Kristina Z.; Dželetović, Milenko U. (Sociološki pregled, 2022)
The paper presents the results of research regarding the attitudes of secondary school students in the Republic of Serbia to the impact of the national security system on the prevention of security threats. The research is based on the method of a semi-structured questionnaire, which includes questions about the influence of the police, army, and intelligence services on the prevention of various security threats. The results of the research show that secondary school students perceive the police as a key subject of the national security system, considering the contribution to the prevention of security threats. The police are followed by the military, as the second most important entity, while the intelligence services are perceived as the entity that with the least pronounced impact on the prevention of security threats. Secondary school students perceive corruption, media propaganda, drug abuse, and crime as the predominant security threats, which extremely or to a great extent threaten security.